2020
DOI: 10.3389/fbioe.2020.00809
|View full text |Cite
|
Sign up to set email alerts
|

Single-Sample Node Entropy for Molecular Transition in Pre-deterioration Stage of Cancer

Abstract: A complex disease, especially cancer, always has pre-deterioration stage during its progression, which is difficult to identify but crucial to drug research and clinical intervention. However, using a few samples to find mechanisms that propel cancer crossing the pre-deterioration stage is still a complex problem. In this study, we successfully developed a novel single-sample model based on node entropy with a priori established protein interaction network. Using this model, critical stages were successfully d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Based on a previous study, DNB members have been considered leading factors, situated at important positions of pathways that regulate vital immune-associated processes during cell differentiation initiation and development ( 20 , 21 ). DNB members could affect DNB-neighboring genes.…”
Section: Resultsmentioning
confidence: 99%
“…Based on a previous study, DNB members have been considered leading factors, situated at important positions of pathways that regulate vital immune-associated processes during cell differentiation initiation and development ( 20 , 21 ). DNB members could affect DNB-neighboring genes.…”
Section: Resultsmentioning
confidence: 99%
“…However, similar to non-coding RNAs regarded as the ‘dark matter’ in sequence, some non-DEGs may be involved in the essential biological processes of disease progression and should not be ignored. It has been reported that some dark genes’ are enriched in key functional pathways ( Han et al, 2020 ) and perform well in prognosis ( Liu et al, 2020 ). To discover such dark genes, the Kaplan–Meier (log-rank) survival analysis of sNMB values and that of gene expression were compared based on the signaling genes (top 5% of genes with the highest local sNMB values) that were not differentially expressed at the critical point.…”
Section: Resultsmentioning
confidence: 99%
“…Axonal regeneration of the injured central nervous system after injury is affected by immune cells ( 43 ). Cellular activity can be characterized by molecular and their interactions within the cells, so is similar to the process of signal transmission ( 45 ). Autophagy participates in intercellular communication, mediates the secretion of nonclassical proteins ( 46 ), and regulates the function of immune cell function ( 47 ).…”
Section: Discussionmentioning
confidence: 99%